(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective: Aim was to compare the time taken towards successful tracheal intubation using a stylet or gum elastic bougie in a simulated difficult airway. Study Design: Randomized control trial Place and Duration: This study was conducted at Tertiary Care Hospital in Peshawar and the duration of this study was from January 2017 to January 2018. Methods: Total 78 patients of elective surgical procedure requiring tracheal intubation were included in this study. Detailed demographics of enrolled cases were recorded after taking informed written consent. Patients were equally divided in two groups. Group I received gum elastic bougie for intubation in 39 cases and 39 cases of group II received stylet intubate. The results of both groups' intubation attempts and total success rates were then compared. Implementation of the Chi-Square test and Students' T-test was used for statistical analysis. SPSS 23.0 was used to analyze all data. Results: In 78 cases, 54 (69.2%) were males and 24 (30.8%) were females. Patients mean age was 27.9±10.89 years and had mean BMI 23.8±4.38 kg/m2. We found a higher number of intubated cases in group I 38 (97.4%) as compared to group II in 31 (79.5%) cases with p value <0.005. Mean time of intubation in group I was 22.3±8.44 sec and in group II was 26.7±14.49 sec. Frequency of intubated cases in first attempt was also higher in group I 30 (76.9%) as compared to group II found in 18 (46.2%) with p value <0.003. There was no any significantly difference found in complications among both groups. Conclusion: Tracheal intubation with a gum-elastic bougie had a greater success rate than stylet aided intubation in the simulated difficult airway and ought to be used in a difficult intubation situation.